A novel organizational model to face the challenge of multimorbid elderly patients in an internal medicine setting: a case study from Parma Hospital, Italy - Meschi, Tiziana; Ticinesi, Andrea; Prati, Beatrice; Montali, Arianna; Ventura, Antonio; Nouvenne, Antonio; Borghi, Loris (Internal and emergency medicine, 2016)
Continuous increase of elderly patients with multimorbidity and Emergency Department (ED) overcrowding are great challenges for modern medicine. Traditional hospital organizations are often too rigid to solve them without consistently rising healthcare costs. In this paper we present a new organizational model achieved at Internal Medicine and Critical Subacute Care Unit of Parma University Hospital, Italy, a 106-bed internal medicine area organized by intensity of care and specifically dedicated to such patients. The unit is partitioned into smaller wards, each with a specific intensity level of care, including a rapid-turnover ward (mean length of stay <4 days) admitting acutely ill patients from the ED, a subacute care ward for chronic critically ill subjects and a nurse-managed ward for stable patients who have socio-economic trouble preventing discharge. A very-rapid-turnover (“come’n’go”) ward has also been instituted to manage sudden ED overflows. Continuity, effectiveness, safety and appropriateness of care are guaranteed by an innovative figure called “flow manager,” with skilled clinical experience and managerial attitude, and by elaboration of an early personalized discharge plan anticipating every patient’s needs according to lean methodology principles. In 2012–2014, this organizational model, compared with other peer units of the hospital and of other teaching hospitals of the region, showed a better performance, efficacy and effectiveness indexes calculated on Regional Hospital Discharge Records database system, allowing a capacity to face a massive (+22 %) rise in medical admissions from the ED. Further studies are needed to validate this model from a patient outcome point of view.